A new species of Schindler’s fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria - Ahnelt, Harald; Sauberer, Michael (Zootaxa, 2018)
Schindleria macrodentata sp. nov., a new species of the paedomorphic gobiid fish genus Schindleria, is described from the Malay Archipelago. The two specimens were collected in 1929 during the “Dana Expedition” in the Molucca Sea between Sulawesi and Halmahera islands (00°29′N, 125°54′E) (Indonesia) and in the Sulu Sea close to Panay Island (11°43’N, 121°43′E) (Philippines). The new species is characterized by a slender body (body depth at pectoral fin base 3.6–3.7 % of SL and at anal fin origin 3.9–4.8 % of SL), a long second dorsal fin (first dorsal fin absent) originating distinctly anterior to the origin of the anal fin (predorsal length 61.8–65.2 % of SL and preanal length 71.7–75.8 % of SL), a short tail (from anus to tip of longest caudal fin ray) (22.1 % of SL), 19–20 dorsal fin rays and 10 anal fin rays, first anal fin ray below 9th dorsal fin ray, few large, widely spaced teeth in the upper and the lower jaws (7 on the premaxilla and 6 on the dentary), an elongated pectoral radial plate (length 3.7–4.5 % of SL) and, in the caudal skeleton, a procurrent ray with an additional spiny process at its base. No distinct urogenital papilla and no pigmentation on body are developed. In this study we present three morphological traits until now not considered as diagnostic characters for Schindleria, the shape of the pectoral radial plate, the shape of the last procurrent caudal spine and the shape of the arch formed by the lower jaw. We also discuss the caudal-fin skeleton of Schindleria, a character developing beyond the larval stages. The record of S. macrodentata is the first of the genus Schindleria for Indonesia and, at more than 100 km distant to the next shore, it is the first offshore record of a Schindler’s fish.